solve the given equations using exact differential
equations.
1. (6x + y2)dx + y(2x − 3y)dy = 0
2. (y2 − 2xy + 6x)dx − (x2 − 2xy + 2)dy = 0, when x = 1, y = 2
3. v(2uv2 − 3)du + (3u2v2 − 3u + 4v)dv = 0, when u = 1, v = 1
4. (1 + y2 + xy2)dx + (x2y + y + 2xy)dy = 0
5. (w3 + wz2 − z)dw + (z3 + w2z − w)dz = 0, when w = 4, z = 2
"\\displaystyle\n(6x+y^2 )dx - (2xy - 3y^2)dy= 0\\\\\n\\text{Let $M = 6x+y^2 $ and $N = 2xy - 3y^2$}\\\\\n\\text{Let $F(x,y) = \\int (2xy - 3y^2)dy$}\\\\\n\\implies F(x,y) = xy^2-y^3 + h(x)\\\\\n\\text{Differentiating and equating it to M, we have}\\\\\ny^2 +h'(x) = y^2+6x\\\\\n\\implies h'(x) = 6x\\\\\nh(x) = 3x^2\\\\\n\\therefore F(x,y) = xy^2-y^3 + 3x^2\\\\\n\\text{The solution to the exact differential equation is}\\\\\nxy^2-y^3 + 3x^2=c\\\\\n2.\n(y^2-2xy+6x)dx - (x^2-2xy+2)dy= 0\\\\\n\\text{Let $M = y^2-2xy+6x $ and $N = -(x^2-2xy+2)$}\\\\\n\\text{Let $F(x,y) = \\int -(x^2-2xy+2)dy$}\\\\\n\\implies F(x,y) = -x^2y+xy^2-2y + h(x)\\\\\n\\text{Differentiating and equating it to M, we have}\\\\\ny^2 -2xy+h'(x) = y^2-2xy+6x\\\\\n\\implies h'(x) = 6x\\\\\nh(x) = 3x^2\\\\\n\\therefore F(x,y) =-x^2y+xy^2-2y+ 3x^2\\\\\n\\text{The solution to the exact differential equation is}\\\\-x^2y+xy^2-2y+ 3x^2=c\\\\\n\\text{When x= 1, y=2, c = 1, therefore the particular solution is}\\\\\n-x^2y+xy^2-2y+ 3x^2=-1\\\\\n3.\nv(2uv^2-3)du + (3u^2v^3-3u+4v)dv= 0\\\\\n\\text{Let $M = v(2uv^2-3) $ and $N = 3u^2v^2-3u+4v$}\\\\\n\\text{Let $F(u,v) = \\int (2uv^3-3v)du$}\\\\\n\\implies F(u,v) = u^2v^3-3uv + h(v)\\\\\n\\text{Differentiating and equating it to M, we have}\\\\\n3u^2v^2-3u+h'(x) = 3u^2v^2-3u+4v\\\\\n\\implies h'(v) = 4v\\\\\nh(v) = 2v^2\\\\\n\\therefore F(u,v) =u^2v^3-3uv+ 2v^2\\\\\n\\text{The solution to the exact differential equation is}\\\\u^2v^3-3uv+ 2v^2=c\\\\\n\\text{When u = 1, v=1, c = 0, therefore the particular solution is}\\\\\nu^2v^3-3uv+ 2v^2=0\\\\\n4.\n(1+y^2+xy^2)dx + (x^2y+y+2xy)dy= 0\\\\\n\\text{Let $M = 1+y^2+xy^2 $ and $N = x^2y+y+2xy$}\\\\\n\\text{Let $F(x,y) = \\int x^2y+y+2xydy$}\\\\\n\\implies F(x,y) = \\frac{x^2y^2}{2}+\\frac{y^2}{2}+xy^2 + h(x)\\\\\n\\text{Differentiating and equating it to M, we have}\\\\\ny^2+xy^2+h'(x) = 1+y^2+xy^2\\\\\n\\implies h'(x) = 1\\\\\nh(x) = x\\\\\n\\therefore F(x,y) =\\frac{x^2y^2}{2}+\\frac{y^2}{2}+xy^2 +x\\\\\n\\text{The solution to the exact differential equation is}\\\\-x^2y+xy^2-2y+ 3x^2=c\\\\\n5.\n\n(w^3+wz^2-z)dw + (z^3+w^2z-w)dz= 0\\\\\n\\text{Let $M = w^3+wz^2-z $ and $N = z^3+w^2z-w$}\\\\\n\\text{Let $F(w,z) = \\int w^3+wz^2-zdw$}\\\\\n\\implies F(w,z) = \\frac{w^4}{4}+\\frac{w^2z^2}{2}-wz+h(z)\\\\\n\\text{Differentiating and equating it to M, we have}\\\\\nw^2z-w+h'(x) = z^3+w^2z-w\\\\\n\\implies h'(x) = z^3\\\\\nh(z) = \\frac{z^4}{4}\\\\\n\\therefore F(x,y) =\\frac{w^4}{4}+\\frac{w^2z^2}{2}-wz+\\frac{z^4}{4}\\\\\n\\text{The solution to the exact differential equation is}\\\\\\frac{w^4}{4}+\\frac{w^2z^2}{2}-wz+\\frac{z^4}{4}=c\\\\\n\\text{When w= 4, z=2, c = 92, therefore the particular solution is}\\\\\n\\frac{w^4}{4}+\\frac{w^2z^2}{2}-wz+\\frac{z^4}{4}=92"
Comments
Leave a comment